Perception on environmental strategies and the impact toward green purchase intention / Zainora Mohd Isa - Mohd Isa, Zainora (2013)
Environmental strategies also known as environmental management practices that adopted by hotel management which help them to monitor their activities in order to preserve the environment. However, these strategies which include energy management, water conservation and waste management have their own impact toward customer green purchase intention. Understanding customer perception toward green product is crucial to attract customer in purchasing environmental-friendly hotel. This paper using self-administered questionnaire adapted from previous researchers with total of 400 respondents. From the findings, it showed that most of the respondents agreed that ‘designing parking areas under the hotel’s building to reduce site footprint’, ‘fixing toilet leaks immediately’ and ‘encouraging recycling campaign by using refillable amenities’ as the three main agreeable items in the environmental strategies. Most of the respondents also agreed that they were willing to stay in a hotel that practices environmental strategies. Importance implications for hoteliers and academicians been discussed through the investigation of this study.